IMPLEMENTATION OF TECHNOLOGY FOR THE USE OF SUBSTANDARD SEMICONDUCTOR STRUCTURES FOR THE MANUFACTURE OF SOLAR CELLS - Kritskaya, Tetyana; Nebesniuk, Oksana; Nikonova, Alina; Nikonova, Zoya (Scientific Journal "Metallurgy", 2023)
Solar energy is one of the most promising and dynamic renewable energy (RES). Each year, the increase in capacities that are commissioned is approximately 40–50 %. In total, in the last fifteen years, the proportion of solar electricity in the world energy has exceeded the 5 % mark. Improving the technology of production of photovoltaic modules has led to a significant decrease in electricity cost. In more than 30 countries (in particular, Germany, Chile, Australia, Mexico), solar energy has become cheaper than received from traditional sources (oil, gas, coal). Over the past 10 years, investments in solar energy have amounted to about $ 300 billion. Ukraine takes important steps to expand the use of RES and alternative fuels within its broader strategy to reduce dependence on traditional fossil fuels. The issues of increasing the efficiency of solar energy application are considered. One of the directions is the development of new technologies and the use of cheap material. The technology of creation of photoelectric converters on the basis of inexpensive initial semiconductor materials and creation for them of high-quality contact systems is offered. The technology of production of solar cells with use of ITO-layers is presented. Introduction of the offered technology of production of solar cells can considerably increase competitiveness of domestic production and reduce import of energy resources.